Tzanakis Scoring System in Acute Appendicitis Concern to Indian Population - Yeshwant Lamture1, Rahul Y. Netragaonkar2, Varsha Gajbhiye3, Ranjeet Ambad4 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Background: Acute appendicitis is amongst the most encountered emergencies seen in casualties requiringintervention. The incidence of negative laparotomy is 15% to 25% and is associated with notable morbidity.Scoring systems are useful and logical for distinguishing acute appendicitis from non-specific abdominalpain. Presently many scoring systems exist that aids in the diagnosis of acute appendicitis but still fail todecrease the rates of wrong diagnosis and the negative appendicectomy rate. This study has been undertakento evaluate the efficacy of the Tzanakis scoring system for the Indian population in diagnosing acuteappendicitis.Method and Material: A prospective study to evaluate Tzanakis scoring system on 50 patients. The decisionof an appendicectomy was taken by the consultant surgeon. The outcomes of the Tzanakis scoring system interms of sensitivity, specificity, positive predictive value, negative predictive value, and diagnostic accuracywere calculated.Results: The Tzanakis scoring system had sensitivity, specificity, PPV, NPV, and DA of 71.42%, 66.67%,83.33%, 50%, and 70% respectively.Conclusion: Tzanakis scoring system in diagnosing acute appendicitis has a lower value in Indianpopulations